Association between RC/HDL-C ratio and risk of non-alcoholic fatty liver disease in the United States - Xuan, Yanyan; Hu, Weike; Wang, Yudan; Li, Jingwen; Yang, Lisha; Yu, Songping; Zhou, Dongdong (Frontiers in Medicine, 2024)
Background The occurrence of non-alcoholic fatty liver disease (NAFLD) is increasing worldwide. The link between serum remnant cholesterol (RC) to high-density lipoprotein cholesterol (HDL-C) ratio and NAFLD remains unclear. Therefore, we sought to clarify the relationship between the RC/HDL-C ratio and the NAFLD. Methods Data for our cross-sectional study came from the 2017–2018 National Health and Nutrition Examination Survey (NHANES) with 2,269 participants. Associations between RC/HDL-C levels and the prevalence of NAFLD and hepatic fibrosis were evaluated using adjusted multivariate logistic regression analyses. A generalized additive model examined the non-linear relationship between RC/HDL-C and the probability of developing NAFLD. Results Among 2,269 participants, 893 (39.36%) were diagnosed with NAFLD. In each of the three models, RC/HDL-C and NAFLD had a strong positive statistical relationship: model 1 (OR = 9.294, 95%CI: 6.785, 12.731), model 2 (OR = 7.450, 95%CI: 5.401, 10.278), and model 3 (OR = 2.734, 95%CI: 1.895, 3.944). In addition, the subgroup analysis by gender and BMI suggested that RC/HDL-C showed a positive correlation with NAFLD. The RC/HDL-C ratio was positively correlated with the degree of liver steatosis. There was an inverted U-shaped connection between the prevalence of NAFLD and RC/HDL-C, with an inflection point of 0.619 for all participants and 0.690 for men. Receiver operating characteristic (ROC) analysis showed that the predictive value of RC/HDL-C for NAFLD (area under the curve: 0.7139; 95%CI: 0.6923, 0.7354; P < 0.001), was better than traditional lipid parameters. Conclusion Increased RC/HDL-C levels are independently associated with an increased risk of NAFLD and the severity of liver steatosis in the American population. In addition, the RC/HDL-C ratio can be used as a simple and effective non-invasive biomarker to identify individuals with a high risk of NAFLD.